Ruwatan: Upacara Pembebasan Malapetaka Tinjauan Sosiokultural Masyarakat Jawa - Darmoko, Darmoko (UI Scholars Hub, 2002)
The religion of Javanese society views that the universe as the wholeness which is balanced and harmonious, inseparable one from another, and always interconnected. The universe consists the macrocosm and microcosm. The macrocosm and the microcosm, are not always stable, but instable. The instability in the macrocosm, is the result of incident made on the surface of microcosm, or on the contrary. The regularity in the microcosm and macrocosm is coordinated, and if each cosm tries to achive unity and harmony, therefore life will be quiet and harmonious. The Javanese society always makes effort to guard harmony in the universe, if it is in chaos, they usually conduct rituals. The ritual of ruwatan is an effort in Javanese society to make the universe balance. Because of the incident affected by sukerta, therefore man has to be rid of the accident (to be eaten by Batara Kala). In the ruwatan ritual is usually performed presenting Murwakala or Sudamala scemes.